ANALISIS JARINGAN KOMUNIKASI PETANI TANAMAN SAYURAN (KASUS PETANI SAYURAN DI DESA EGON, KECAMATAN WAIGETTE, KABUPATEN SIKKA, PROVINSI NUSA TENGGARA TIMUR) - Bulkis, Bulkis (Jurnal Matematika Sains dan Teknologi, 2015)
In order to improve production and quality of vegetables, farmers need adequate information and reliable sources of information to achieve their goals. Meet their information needs on the behavior of vegetable farming;  farmers need to establish a network of communication among farmers. The purpose of this study was: (1) to describe the communication network among vegetable farmers in the village of Egon (2) to analyze the relationship between the characteristics of farmers and communication networks. The unit of analysis is a vegetable farmer. Samples of study are fifty-three farmers sampled using the census. Primary data collection and field observations were conducted during June to July 2012.  Data used in this study consisted of primary and secondary data. Sociometric analysis is used to view network communications occur among vegetable farmers. Communication network structures were analyzed using UCINET VI. Data analysis was performed by using Microsoft excel and followed by Spearman rank correlation analysis by using SPSS for windows.  The results show that: (1) the description of communication network of vegetable farmers are  radial personal network and interlocking personal network , while crop protection communication networks and communication networks of harvest and post harvest is central personal network (2)  there was a relation between farmer’ non formal education, farming experience, cosmopolitan level, land area, and tenure with network communications.Dalam rangka meningkatkan produksi dan kualitas sayuran, petani membutuhkan informasi yang memadai dan sumber informasi yang terpercaya untuk mencapai tujuan mereka. Untuk memenuhi kebutuhan informasi mereka tentang perilaku usahatani tanaman sayuran, petani membangun jaringan komunikasi antarpetani. Artikel ini membahas (1) gambaran jaringan komunikasi diantara petani sayuran di desa Egon, dan (2) hubungan antara karakteristik petani dengan jaringan komunikasi. Lima puluh tiga petani diambil sebagai sampel dengan menggunakan metode sensus. Pengumpulan data primer dan observasi lapangan dilakukan selama bulan Juni sampai Juli 2012. Data yang digunakan dalam penelitian ini terdiri dari data primer dan sekunder. Analisis sosiometri digunakan untuk melihat jaringan komunikasi yang terjadi di antara petani sayuran. Struktur jaringan komunikasi dianalisis dengan menggunakan UCINET VI. Analisis data dilakukan dengan menggunakan program excel dan SPSS for windows, yaitu analisis korelasi Person dan Rank Spearman. Hasil yang diperoleh: (1) gambaran jaringan komunikasi usahatani petani sayuran yang terbentuk adalah jaringan personal radial dan jaringan personal memusat (2) terdapat hubungan antara pendidikan non formal, pengalaman bertani, tingkat kosmopolitan, luas lahan, status kepemilikan lahan dengan jaringan komunikasi.